2018
DOI: 10.1159/000488077
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MDA5 Antibody-Positive Dermatomyositis Presenting with Cellulitis-Like Erythema on the Mandible as an Initial Symptom

Abstract: Panniculitis is an uncommon skin eruption observed in patients with dermatomyositis (DM)/clinically amyopathic dermatomyositis (CADM), especially in anti-melanoma differentiation-associated gene 5 (MDA5) antibody-positive DM. We present here a 51-year-old Japanese woman with an anti-MDA5 antibody-positive DM who initially had cellulitis-like erythema on her right mandible. Histopathological findings showed a subcutaneous lobular infiltration of lymphocytes. The patient developed typical skin eruptions of DM/CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…Some reports have discussed the association between panniculitis and MDA5 (10,11); however, the number of patients has been small, and further studies are needed. We found five case reports of patients with anti-MDA5 antibody-positive DM complicated with panniculitis, and all patients had panniculitis as their initial symptom (12)(13)(14)(15)(16). Our case showed that patients with anti-MDA5 antibodypositive DM can develop panniculitis even during treatment.…”
Section: Discussionmentioning
confidence: 70%
“…Some reports have discussed the association between panniculitis and MDA5 (10,11); however, the number of patients has been small, and further studies are needed. We found five case reports of patients with anti-MDA5 antibody-positive DM complicated with panniculitis, and all patients had panniculitis as their initial symptom (12)(13)(14)(15)(16). Our case showed that patients with anti-MDA5 antibodypositive DM can develop panniculitis even during treatment.…”
Section: Discussionmentioning
confidence: 70%
“…Anti‐melanoma differentiation‐associated gene 5 antibody‐associated dermatomyositis (MDA5‐associated DM) is a rare subgroup of idiopathic inflammatory myositis, presenting with cutaneous features of classical dermatomyositis (DM), but no or minimal involvement of the proximal muscles. Numerous cases of DM associated with MDA5 antibodies have been described in the literature, emphasising the need for early diagnosis in this rare entity which may be overlooked due to substantially different clinical presentations . More importantly, the prognosis can be extremely poor due to high incidence of rapidly progressive interstitial disease (RP‐ILD) in these patients.…”
mentioning
confidence: 99%
“…In a case series of 3 patients described by Kume et al [6], they also found that this unilateral heliotrope rash was only seen in DM patients with MDA-5 antibodies, preceded the usual manifestations of DM, and could be associated with rapidly progressive interstitial lung disease. Another unique early finding that has been reported in MDA-5 DM is lobular panniculitis of the cheek or mandible [7, 8]. In both cases, swelling and unilateral erythema of the angle of the jaw was seen, and correlated with a lobular panniculitis of lymphoplasma-histiocytic infiltrates that rapidly improved with treatment.…”
Section: Discussion/conclusionmentioning
confidence: 91%